Lasersko površinsko kaljenje jekel ter lasersko pretaljevanje površine sive in nodularne litine - Grum, Janez (Kovine zlitine tehnologije, 1998)
Since 1970 a number of investigations have been published on applications of laser in different machining processes and generally in engineering. The present state in the development and in the applications shows that the prevailing laser technologies are laser cutting and laser welding while applications in the field of heat treatment of surface properties of materials are still scarce. The contribution will present some experiences in researching the use of laser in the field of laser surface melt-hardening on gray and nodular irons and surface layer hardening by the method of transformation hardening.
Keywords: kaljenje lasersko; plasti površinske; pretaljevanje plasti; siva litina; litina nodularna; mikrostrukture; potek temperatur; jekla; nodularna litina; lasersko kaljenje; površinsko kaljenje; obdelava materiala